Preparation and Physico-Chemical Investigation Studies for the of Mn(II),Co(II),Ni(II) and Cu(II) Metal Complexes with Ligand 2- Hydroxybenzaldine Urea (Baghdad Science Journal, 2016)
Some of metal compounds have been synthesized of record ligand from aldehid interaction of a substance which is salicyladehyde with another material which is urea. During the analysis of the metal component, The prepared complexes were characterized by elemental analysis, IR ,UV-visible , conductivity and magnetic susceptibility measurements. this confirms the ratio[1:1] between the metal and ligand. It is found that theortical values agree with practical values All the studied complexes are suggested as an octahedral stereochemistry.